Aesthetic treatment on anterior teeth crown fracture caused by dental trauma - Nanik Zubaidah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Complicated crown fracture is a tooth fracture that involve enamel, dentine and pulp. The incidence of complicated crown fracture ranges from 2% to 13% of all dental injuries and the most commonly involved teeth are the maxillary central incisors. Various treatment modalities are available depending on the clinical, physiological and radiographic examination of the involved teeth. Purpose: The aim of this case report is to present the management of crown fractures with pulpal exposure caused by traumatic injury, through endorestoration approach to reconstruct the shape and function of the teeth. Case: A 17 years old male with complicated crown fractures of anterior teeth #11 #21 and #22. The patient wish for aesthetic dental treatment in both of its form and function. Case management: Crown fractures of anterior teeth with exposed pulp caused by traumatic injury were reconstructed by endorestoration approach. The endodontic treatment with post and core insertion in the root canal which will increase its retention and porcelain fused to metal crown which will aesthetically recover its original form and function. After restoration the patient feel very glad and confident with the result. Conclusion: Endorestoration treatment on anterior teeth with complicated crown fractures and exposed pulp is able to recover the normal form, function and dental aesthetic in accordance with stomatognatic system and self confidence.Latar belakang: Fraktur mahkota kompleks (complicated) adalah fraktur pada mahkota gigi yang melibatkan enamel, dentin dan pulpa. Kejadian dari fraktur mahkota kompleks bervariasi antara 2-13% dari semua trauma gigi dan sebagian besar gigi yang terkena adalah gigi insisif pertama rahang atas. Berbagai macam cara perawatan yang dilakukan tergantung pada hasil pemeriksaan klinis, psikologis dan radiografis dari gigi yang terkena. Tujuan: Laporan kasus ini menjelaskan penatalaksanaan fraktur mahkota gigi dengan pulpa terbuka akibat trauma dengan perawatan endorestorasi untuk mengembalikan bentuk dan fungsi gigi. Kasus: Penderita pria umur 17 tahun dengan fraktur mahkota pada gigi anterior #11, #21 dan #22. Penderita tersebut menginginkan perawatan estetik untuk mengembalikan estetik baik bentuk maupun fungsi giginya. Tatalaksana kasus: Fraktur mahkota gigi anterior dengan pulpa terbuka akibat trauma gigi dikembalikan melalui pendekatan perawatan endorestorasi. Perawatan endodontik dengan pasak tuang dan inti yang dimasukkan ke dalam saluran akar akan meningkatkan retensi dan kemudian ditutup dengan mahkota porselen fused to metal dapat mengembalikan bentuk maupun fungsinya. Selesai perawatan, pasien merasa senang dengan hasil perawatan tersebut dan hal ini menunjukkan peningkatan kepercayaan diri pasien. Kesimpulan: Perawatan endorestorasi gigi anterior dengan fraktur mahkota kompleks gigi anterior dengan pulpa terbuka dapat mengembalikan bentuk, fungsi dan estetik yang normal sesuai dengan sistem stomatognatik dan meningkatkan kepercayaan diri.